Pengembangan Multimedia Interaktif Berbantuan Articulate Storyline di Sekolah Dasar - Maharani, Jihan; Firman, Firman; Lisa Aditya Dwiwansyah Musa (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This research explores the needs analysis, validity, practicality and effectiveness of interactive media with the theme "Various Jobs" based on an articulate storyline at SDN 05 Salamae. Using the ADDIE R&D model method, data was collected through interviews, questionnaires and tests, then analyzed qualitatively and quantitatively. This research involved 19 fourth grade students. The findings show that the ongoing learning process requires innovative audiovisual media that answers this theme. The designed media achieved a validity of 91.75%, which means very high validity. Practicality, which involved 19 students and a teacher, scored 94.78% and 97.91% respectively, indicating high practicality. Meanwhile, the test results for the effectiveness of using interactive multimedia are classified as high with an average value of 82.63 Kata Kunci:;;